Postbiotics in the medical field under the perspective of the ISAPP definition: scientific, regulatory, and marketing considerations - Vinderola, Celso Gabriel (2023)
Diverse terms have been used in the literature to refer to the health benefitsobtained from the administration of non-viable microorganisms or their cellfragments and metabolites. In an effort to provide continuity to this emergingfield, the International Scientific Association of Probiotics and Prebiotics (ISAPP)convened a panel of experts to consider this category of substances and adoptedthe term postbiotic, which they defined as a “preparation of inanimatemicroorganisms and/or their components that confers a health benefit on thehost.” This definition does not stipulate any specific health benefit, finishedproduct, target population or regulatory status. In this perspective article, wefocused on postbiotics developed for pharmaceutical uses, including medicinalproducts and medical devices. We address how this field is regulated for productsbased on inanimate microorganisms, marketing considerations and existingexamples of postbiotics products developed as cosmetics for the skin, forvaginal health, and as orally consumed products. We focus on the EuropeanUnion for regulatory aspects, but also give examples from other geographicalareas.